PEMANFAATAN MINYAK JELANTAH MENJADI SABUN CUCI PADA BANK SAMPAH DI KELURAHAN BAMBU APUS PAMULANG - Rini Septiowati; Rakhmawati Oktavianna; Sevty Wahiddirani Saputri; Silvia Sari; Benarda Benarda (Abdimisi, 2019)
Community Service entitled the use of used cooking oil into washing soap at a garbage bank in the Village of Bambu Apus aims to empower and increase the value of used cooking oil that is not used and is usually disposed of into trash, but with this training with simple capital can be processed into washing soap which can be used alone or sold and earn income and improve the living standards of garbage bank members. The target of this service is all members of the garbage bank registered in the Village of Bambu Apus Pamulang, which consists mostly of housewives. The results of this PKM are proven by the women members of the garbage bank Bambu Apus Village that can apply the use of used cooking oil into washing soap properly and can be marketed to consumers by attending exhibitions or marketed around the neighborhood and online.